In-vitro Chemodissolution of Urinary Stones by EDTA Salts - Rao, T.V.R.K.; Das, Maitreyee (Asian Journal of Chemistry, 2016)
Chemodissolutions of ten surgically removed urinary stones were studied in diluted aqueous solutions of some EDTA salts, viz., disodium EDTA, dipotassium EDTA and magnesium EDTA. All the stones studied were of pure oxalate or phosphate or mixed oxalate-phosphate type. Kinetics of dissolution was observed over a period of ten days. Results revealed significant in-vitro solubility of urinary stones in the EDTA salts. Surface activity and chelation specificity seem to be the dominant factors in the process of dissolution.